Deep Learning and Continuous Representations for Natural Language Processing (Tutorial at IJCAI 2016) - Yih, Scott Wen-tau; He, Xiaodong; Gao, Jianfeng (IJCAI 2016, 2016)
This tutorial provides an extensive overview on recently developed techniques in deep learning and continuous-space representations for natural language problems. Approaches to important real-world natural language applications, including machine translation, semantic representation modeling, question answering and semantic parsing will be the main focus.